PENERAPAN METODE CERAMAH PLUS DEMONSTRASI DAN LATIHAN DALAM MATA PELAJARAN PAI MATERI THAHARAH PADA KELAS 7 SMP PGRI 06 MALANG - Shahila Nur Azizah; Khoirul Asfiyak; Bahroin Budiya (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The research focus is structured as follows (1) How is learning planning using the lecture method plus demonstrations and exercises at SMP PGRI 06 Malang?, (2) How is the implementation of learning using the lecture method plus demonstrations and exercises at SMP PGRI 06 Malang? ?, (3) What are the results obtained after learning by using the lecture method plus demonstrations and exercises at SMP PGRI 06 Malang?. This research is a qualitative research and descriptive qualitative research type with the place of research in SMP Pgri 06 MalangBased on the results of the research that has been carried out, the researchers can draw conclusions about the application of the Lecture Plus Demonstration and Exercise Method in the Pie Subjects for Class 7 Thaharah at SMP Pgri 06 Malang, as follows: (1) the planning made before implementing this lecture method is to using lesson plans, and if the planning made before carrying out this demonstration method is to prepare the object to be discussed, while the planning made before doing the exercise method is to prepare questions for evaluation. (2) the implementation of the lecture method itself by explaining the material that has been prepared, while the implementation of the demonstration method is by practicing the material that has been exemplified, while the implementation of the exercise method is by doing questions to evaluate the material. (3) the results obtained when the lecture method is applied are students will get bored quickly because there is no other method interlude especially if the lesson is during the day, the result of applying the demonstration method is that students understand the material faster because the teacher practices the material directly, while the results of the practice method themselves teachers can not guarantee that students understand.